Comparative Study of Skeletal Stability between Postoperative Skeletal Intermaxillary Fixation and No Skeletal Fixation after Bilateral Sagittal Split Ramus Osteotomy: an 18 Months Retrospective Study - Jens Hartlev; Erik Godtfredsen; Niels Trolle Andersen; Thomas Jensen (eJournal of Oral Maxillofacial Research, 2014)
Objectives: The purpose of the present study was to evaluate skeletal stability after mandibular advancement with bilateral sagittal split osteotomy.